656 Pilot study on urinary incontinence rehabilitation using non-invasive methods (Balneo and PRM Research Journal, 2024)
Urinary incontinence affects up to a quarter of the female population at an active age of over 40 years old. The rate increases by 40% for females over 60 years old. Medical rehabili-tation regarding stress, urge or mixed geriatric urinary incontinence pathologies by using physical, non-invasive methods is poorly reported in literature, even though the obtained results are quantifiable, consistent, durable through continuous and periodic exercise. The objectives of rehabilitation of stress urinary incontinence, urge incontinence and mixed stress and urge urinary incontinence are the conscious toning of muscles of the pelvic floor, patient’s awareness of contractions thereof, and the improvement of these patients’ quality of life. Toning the muscles of the pelvic floor is essential in stress urinary incontinence whereas in urge incontinence it may increase urination control. Physical exercises increase the muscle tonus of the pubococcygeus muscles surrounding the vagina and the anus, and whose contraction may stop the evacuated quantity of urine, faeces and gases. The first-line treatment is the Kegel perineal reeducation, with a preventive and curative role in the treatment of urinary incontinence, also during the first and second stage of genital pro-lapse. Reeducation, supervision, guidance, relaxation, and exercise are essential elements in the reduction of urinary incontinence or prolapse in nascent stages. In literature and in practice there are several approaches to pelvic rehabilitation: some are minimally invasive, while others are non-invasive. In the current investigation, a group of elderly patients with stress, neurological or/and mixed urinary incontinence—which was linked to a mild genital prolapse in the female patients—were treated with four minimally invasive and non-invasive techniques. Associated comorbidities were type II diabetes (ADO treated) and a previous ischemic stroke in antecedents. Kegel exercises will be supplemented by transcutaneous electrical neurostimulation. Electrical neurostimulation also brings non painful electrical stimulation thus producing the contraction of the external sphincter muscle of urethra and the levator ani muscle inducing the inhibition of the detrusor mus-cle and of the contraction of the urinary bladder. After a 3-4 week training, subjective improvements and the spacing out of urinations to 3-4 hours are registered. The continuation of treatment up to 2 months (60 days) additionaly improves patients’ functional status, thus substantiating and stabilizing the obtained results over time. Positive outcomes were attained, as the patient was able to effectively complete the pelvic rehabilitation course of action. Urinary losses could be completely eliminated and the number of nighttime bath-room visits was lowered to the recommended physiological threshold (one awakening per night).Keywords: prepuberty, posture abnormalities, scoliosis, somatoscopy, physiotherapeutic assessment